Section 377A repeal: How to handle disagreements - CHAN, David (Institutional Knowledge at Singapore Management University, 2022)
In a commentary, Professor David Chan (SMU Behavioural Sciences Initiative Director and Lee Kong Chian Professor of Psychology) discussed the repeal of Section 377A of the Penal Code and proposed adopting five practical approaches for a more constructive discussion on the emotive issue.